Effect of Education on Clean and Healthy Life Behavior in Diabetes Mellitus Patients on Gangrene Incidence During the Corona Virus-19 Pandemic - Mahesa Burma; Supriadi; Sari, Apriani Susmita (Omni Nursing Journal, 2024)
Background: Diabetes mellitus is the most common disease that causes other diseases or complications, one of which is gangrene.  In connection with the spread of the corona virus-19, this can worsen the health of people with diabetes mellitus if they experience complications, one of which is gangrene.  With that, Clean and Healthy Lifestyle plays a very important role in the daily life of people with diabetes mellitus during the corona virus-19 pandemic to prevent gangrene. Researchers provide interventions in the form of education on clean and healthy living behavior in patients with diabetes mellitus. Objective: This study aims to determine the effect of education on clean and healthy living behavior in patients with diabetes mellitus on the incidence of gangrene during the corona virus-19 pandemic. Methods: This research was conducted with a pre-experimental approach with the One Group Pretest-Postest Design.  The sample used is 58 respondents with stratified random sampling technique. Analysis of the data used is the Mc Nemar test. Results: Based on statistical tests using the Mc Nemar test, the value of p-value or significant is 0.004 <0.05 which means there is an effect of education on clean and healthy living behavior in diabetes mellitus patients on the incidence of gangrene during the corona virus-19 pandemic. Conclusion: Education on clean and healthy behavior positively influenced diabetes mellitus patients in preventing gangrene during the COVID-19 pandemic. The intervention encouraged improved self-care practices, particularly in foot care, hygiene, and lifestyle management, thereby reducing the risk of complications. These findings highlight the importance of integrating preventive education into diabetes care, especially during public health crises.